Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Passing Bawah Bola Voli Siswa Kelas V MI Islamiyah Kedungwaru - Pratama, Bima Yudha; Utomo, Andy Widhiya Bayu; Wahyudi, Arief Nur (Civiliza Publishing, Indonesia., 2023)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model on the Volleyball Underhand Passing Ability of Class V MI Islamiyah Kedungwaru. This study uses an experimental method to compare the volleyball underhand passing ability of class V MI Islamiyah Kedungwaru students with the problem based learning model, involving 20 students with an analysis of the validity, reliability, internal consistency, balance, and discrimination test instruments before data collection. The results showed that the use of the problem based learning model in teaching volleyball underhand passing ability to class V MI Islamiyah Kedungwaru students had a positive impact. Students who learned through this model showed an increase in their abilities after going through a series of pretests and posttests. This learning model allows students to actively solve real problems related to volleyball, deepen their understanding of concepts, and develop critical thinking skills and problem-solving abilities. In addition, problem-based learning also improves teamwork and student motivation in learning volleyball.